Simple and Green Vortex-Assisted Switchable Solvent Liquid Phase Microextraction for the Determination of Indium in Soil with Matrix Matching and Slotted Quartz Tube (SQT) - Flame Atomic Absorption Spectrometry (FAAS) - Turan, Nouha Bakaraki; Zaman, Buse Tugba; Bakirdere, Emine Gulhan; Kartoglu, Bedrihan; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2020)
A novel preconcentration methodology to enhance the sensitivity of a flame atomic absorption spectrometer for indium determination was investigated in this study. The proposed methodology is based on the application of switchable solvent based liquid-phase microextraction combined with a slotted quartz tube. The isolation of indium was performed using N, N-dimethylbenzylamine as the extraction solvent after complexation with (E)-2,4-dibromo-6-(((3-hydroxyphenyl)imino)methyl)phenol. The detection power was enhanced by approximately 169-fold using the developed method with respect to the conventional flame atomic absorption spectrometry system. The quantification and detection limit values were 28.3 and 8.4 ng mL(-1), respectively. The assessment of several interfering ions on the analyte was performed, and spike experiments were used to validate the method's accuracy. Interferences were observed for a ratio of 1:10 analyte:interferent with a value of 27%. The recovery results obtained using matrix matching strategy indicated the applicability of the developed method for soil matrices.
Keywords: (E)-2; 4-dibromo-6-(((3-hydroxyphenyl)imino)methyl)phenol; indium; slotted quartz tube - flame atomic absorption spectrometry (SQT-FAAS); soil; switchable solvent-based liquid phase microextraction; EXTRACTION PROCEDURE; PALLADIUM; GALLIUM; SPECTROPHOTOMETRY; PRECONCENTRATION; DESIGN; Chemistry